2016
DOI: 10.1016/j.yexcr.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast spheroids as a model to study sustained fibroblast quiescence and their crosstalk with tumor cells

Abstract: Stromal fibroblasts have an important role in regulating tumor progression. Normal and quiescent fibroblasts have been shown to restrict and control cancer cell growth, while cancer-associated, i. e. activated fibroblasts have been shown to enhance proliferation and metastasis of cancer cells. In this study we describe generation of quiescent fibroblasts in multicellular spheroids and their effects on squamous cell carcinoma (SCC) growth in soft-agarose and xenograft models. Quiescent phenotype of fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In fact, in these situations several proteases, destroying ECM structure, liberate fibroblasts from ECM and trigger fibroblasts clusters formation. 9 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, in these situations several proteases, destroying ECM structure, liberate fibroblasts from ECM and trigger fibroblasts clusters formation. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Further, quiescent muscle stem cells are known to secrete CIAPIN 1 to maintain the satellite cells (Chan et al, ). While most of the above described studies, on role of cytokines/chemokines, were done in quiescent stem cells, a recent report showed that quiescent fibroblasts also show an inflammatory secretory phenotype similar to senescence (Salmenperä, Karhemo, Räsänen, Laakkonen, & Vaheri, ). Our study now emphasizes a role of quiescence‐associated secretory phenotype (QASP) as an important characteristic feature of even transient growth arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Human colon Matrigel -rich in growth factors, signal factors for cell proliferation -expensive and animal derived PC-3M, PrCa, NCI-H600 [74], HepG2 [75], A235, B16F10 [76] agar -damage on cells by forces from gel formation inside the agar -excellent mechanical properties human foreskin dermal fibroblasts [77], cortical cell [78] alginate -rapid formation of hydrogel scaffolds -strong chemicals required to break hydrogel networks to harvest MCSs human fat-derived stromal vascular fraction cells [79], human colon cancer cells (HCT116) [80] fibrin -promoting cell attachment -high cell viability human mesenchymal stem cell [81], B16-F1…”
Section: Micro-mouldingmentioning
confidence: 99%